Nilai Islam Dalam Media (Analisis Wacana Kritis Film Hati Suhita) - Fitria, Ninis; Rio Febriannur Rachman (Jurnal Spektrum Komunikasi, 2024)
This study discusses the Islamic values contained on the media in the form of the film Hati Suhita. with a relatively large audience of 507,167 in 2023. The aim of this study is to reveal the da'wah discourse and the Islamic values contained in the film. There are a number of theories used, including the da'wah theories popularized by Ansari and Asmuni Syukur. The theories discuss "maddah" or material and "wasilah" or media. Another theory used in this study is about the basic Islamic values which were popularized by Hadi Yasin and Muhammad Quraish Shihab. The Islamic values discussed in the theory regarding aqidah, sharia, and akhlak. This study is qualitative research with Norman Fairclough's critical discourse analysis approach. Data collection was carried out by text analysis, observing the production team's statements, as well as extracting audience opinions through surveys and interviews. The results of this study show, 1) strengthening the Islamic message in the film was carried out from the preparation period in the production process; 2) Islamic messages about aqidah, sharia and morals can be received directly by the audience; 3) da'wah discourse with the main values of Islamic teachings packaged with narratives of relationships among characters.